Correlation of Demographic Characteristics to Bone Calcium and Vitamin D in Patient taking Proton Pump Inhibitor (PPI): Demographics and Bone Health in Proton Pump Inhibitor Users - Memon, Yasra; Shaikh, Imran Ali; Karim, Imran; Shaikh, Tariq Zaffar (Pakistan Journal of Health Sciences, 2024)
Proton pump inhibitor (PPI) works by blocking the hydrogen-potassium ATPase inhibitor H/K ATPase inhibitor located on gastric parietal cells. It blocks the last step of acid production that is why it is more potent and effective than other acid suppressants like H2 blockers, 99% of gastric acid secretion is reduced by using it. Objective: To evaluate Demographic characteristics of individuals using proton pump inhibitor (PPI) all over Sindh. Methods: The Quasi experimental study contained 227 young individuals of age 20-45years having acid peptic disease, dyspepsia. Study was taken place in Medicine OPDs of Jamshoro and Hyderabad at Civil Hospital and duration of study was from 15th March 2020 to 15th September 2020. All individuals taking proton pump inhibitor were excluded from study. Sampling technique was non-probability convenient sampling. SPSS version 21.0 software was used to analyze the data. The student paired t test was used at the confidence interval of 95%, apart from it the P-value is observed ≤ 0.05. Results: There was no effect on demographic characteristics of individuals using proton pump inhibitor (PPI) all over Sindh on serum calcium and vitamin D levels. Therefore, p-value was seen 0.7 for the serum calcium and 0.1 for Serum Vitamin D. Conclusions: In any group of age, gender, residential status there is no effect on serum calcium and vitamin D with use of proton pump inhibitor (PPI) for less than 6 months.